Teatro e centro de apresentações flutuante: uma nova opção de cultura contemporânea para as comunidades do interior - Moss, Lorena Breda (Brasil, 2025)
Culture is the key to a promising society, where the population is able to balance work with leisure and enjoy what is offered by the location where they live. Unfortunately, during the theoretical technical in-depth study carried out, it was found that of the 10 most populous municipalities in Amazonas, only 4, including the capital, have theaters with adequate structure to host artistic events such as performances, ballet and film screenings. Furthermore, it is common knowledge that it is difficult to reach most of the cities in the interior of Amazonas, the only access to which is via river. Considering these aspects, a floating theater was designed consisting of a modular structure so that all cities have the opportunity to receive the project on their beach, port or pier. The structure uses sustainable resources to maintain its operation and construction technologies that do not generate post-construction waste, thus minimizing the environmental impact of the location where it will be located.